Assessing environmental degradation in a tropical watershed: Evidence from artisanal and small-scale gold mining (ASGM), and plantation expansion in West Kalimantan, Indonesia - Desmaiani, Herda; Akbar, Aji Ali; Romiyanto, Romiyanto; Hermawati, Ery; Suhartoyo, Aji; Rahma, Syafira Nur; Jati, Dian Rahayu; Saziati, Ochih; Sulastri, Aini; Jumiati, Jumiati (Journal of Degraded and Mining Lands Management, 2026)
This study presents a systematic environmental assessment of the Raya River Sub-Watershed in West Kalimantan, Indonesia, from 2018 to 2025. It addresses a critical data gap in a region heavily impacted by artisanal and small-scale gold mining (ASGM) and oil palm expansion. Establishing the first multi-year physicochemical and sedimentological dataset for this tropical catchment enables the identification of key drivers of ecosystem degradation. An analysis was conducted across nine strategic sampling points, with results indicating significant acidification (pH 4.10), elevated total suspended solids (up to 125 mg/L), and heavy metal concentrations in sediments exceeding international quality standards. Utilising X-ray fluorescence (XRF) spectroscopy, the study quantified community exposure to Pb (13.0-45.5 ppm), Fe (290.0-642.3 ppm), Sn (16.0-22.8 ppm), and Mn (67.9-233.0 ppm), signalling persistent toxicological risks. This research establishes a link between in-situ pollution monitoring and human health implications by associating ASGM with agricultural runoff and potential bioaccumulation. These findings provide a scientifically robust baseline, essential for informing targeted remediation strategies, including phytoremediation and erosion control, and for offering a framework for evidence-based environmental governance in contaminated tropical watersheds.